Effects of Virtual Reality on Pain, Anxiety, Patient Satisfaction in Coronary Angiography: A Randomized Trial - Turan, Gulcan Bahcecioglu; Gur, Fatma; Ozer, Zulfunaz; Tarkan, Caglar (Elsevier Science Inc, 2024)
Background: Since patients are conscious during the coronary angiography procedure, they may experience pain and anxiety regarding possible complications and an uncertain outcome. Aim: This study was conducted to determine the effects of virtual reality application on pain severity, anxiety level, and patient satisfaction in patients who undergo coronary angiography. Method: This randomized controlled study was conducted with a total of 70 patients, including 35 patients in the intervention and 35 patients in the control group. Apart from their routine treatment, virtual reality glasses application was used in the intervention group patients during the procedure. The patients in the control group were given only routine treatment. Data were collected by using Descriptive Information Form, Visual Analogue Scale (VAS), Anxiety Assessment Scale (AAS), Physiological Symptoms of Anxiety Follow-up Form, and Virtual Reality Glass Application Satisfaction Form. Results: Mean post-intervention scores of VAS, AAS, heart rate, diastolic and systolic blood pressure, respiratory rate of the intervention group decreased significantly compared with the control group, while O2 saturation value was found to increase significantly. Conclusions: In this study, it was found that virtual reality application was effective in reducing pain and anxiety, increasing patient satisfaction, and normative regulation of vital signs in patients who undergo coronary angiography. (c) 2023 American Society for Pain Management Nursing. Published by Elsevier Inc. All rights reserved.
Keywords: Cardiac-Catheterization; Management; Fear